Kreativitas Kode Visual Golek Asep Sunandar Sunarya dalam Media TV - Irfansyah Irfansyah; Priyanto Sunarto (Wimba : Jurnal Komunikasi Visual, 2013)
'Golek' show is a typical Sundanese art that had been built for generations by the convention (golek as a puppet made from wood that can moved). Convention as the reference in the performance golek set to 'standar' or 'tetekon'. Standard be 'rules' or 'code' in the making and golek play. Previously, the golek show was held in open spaces and performed at night until early morning. Nowdays, staged golek becomes shorter only take place within 2-3 hours. Since the television media increasingly showing its existence; and as well as the emergence of other entertainment stage such as 'dangdut', pop music, 'Malay orchestra', or 'solo organ'.In such condition, there was emergence of Golek Stage by Asep Sunarya. He creates breakthoughs by designing many tricks in his wayang-golek show: character smoking, dancing 'jaipongan', doing material arts pencak silat, or spewing noodle. Asep's wayang golek-performance can regain the attention of the people (mosly Sundanese). On the top of that, Asep style becoming new inspiration for other dalang. The evolving of Asep's golek show, then attracted television industry. At this point, the show becoming more entertaintment than before. In television, golek show perform new encoding, like advertizing code, interaactive broadcasting code, and digital visual effect code.The aim of this study is to reveal the convertion of traditional-golek visual code to modern-television visual-code. The methodologies used are structural visual code, and also ethnometodologi approach. Ethnometodologi method used observation's in-depth interview, and unstructural interview upon selective omnicient informants.